Synodus cresseyi Prokofiev, 2008, an unnecessary replacement for S. macrocephalus Cressey, 1981, and a description of a new species from the Western Indian Ocean (Teleostei: Synodontidae) - Ho, Hsuan-Ching; Prokofiev, Artém M.; Shao, Kwang-Tsao (Zootaxa, 2010)
Synodus cresseyi Prokofiev, 2008 is an unnecessary replacement name for S. macrocephalus Cressey, 1981 according to Article 23.9.5 of the International Code of Zoological Nomenclature. The material used for the description of S. cresseyi includes two species. One of them represents a new species which differs from its congeners in the following combination of characters: anterior palatine teeth not longer than posterior teeth; preopercle scaled posterior to corner of mouth; membranous posterior flap of anterior nostril slender, with a pointed tip, reaching to above posterior nostril when laid back; pectoral fins reaching a line connecting dorsal and pelvic fin origins; pelvic process broad; color in alcohol without any marking, deep brown on dorsal surface restricted to central two-third of head and body, about two scale rows above lateral line, lateral and ventral surface uniformly silver white without blotches.